A survey of attitudes of Turkish veterinary students and educators about animal use in research - Yerlikaya, H; Ozen, A; Yasar, A; Armutak, A; Ozturk, R; Bayrak, S; Seker, I (Czech Academy Agricultural Sciences, 2004)
In this study, veterinary students and veterinary educators from Firat Veterinary School, Istanbul Veterinary School and Selcuk Veterinary School were surveyed to evaluate their attitudes to animal use in research. Data were collected from 330 students and 204 educators by personal interviews. All participants showed anthropocentric attitudes toward animal use in research. Most of the participants agreed on items regarding the animal tests being easier, more scientific, more common, more economical and more reliable than alternative methods, but they also signified that they did not agree with the item indicating that the animal experimentation is more conscience. In conclusion, we can state that both the veterinary students and the educators are in a complete dilemma in the discussions regarding the animal experimentation. In order to avoid the negative circumstances that can arise from this dilemma, it could be said that veterinary schools should be supported in this aspect with related courses to be included within their curriculum.
Keywords: experimental animal; ethics; Turkey